2021
DOI: 10.1111/deve.12274
|View full text |Cite
|
Sign up to set email alerts
|

Do Lockdown Policies Reduce Economic and Social Activities? Evidence from NO2 Emissions

Abstract: This study empirically investigates how much economic and social activities were decreased by the implementation of lockdown policies during the coronavirus disease 2019 (COVID-19) pandemic. We measure the magnitude of those activities using nitrogen dioxide (NO2) emissions. Our observations include daily NO2 emissions in 173 countries from January 1 to July 31, 2020. Our findings can be summarized as follows. Lockdown policies significantly decreased NO2 emissions in low-income countries during policy and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…So far, most of the existing literatures related to the environmental impact of COVID-19 focused on quantifying the concentration change of atmospheric pollutants in the global context ( Bai et al, 2020 ; Deb et al, 2020 ; Le et al, 2020 ; Dang and Trinh, 2021 ; Keola and Hayakawa, 2021 ; Liu et al, 2021c ; Nguyen et al, 2021 ; Smith et al, 2021 ; Venter et al, 2020 ), countries ( Bao and Zhang, 2020 ; Berman and Ebisu, 2020 ; He et al, 2020 ; Petetin et al, 2020 ; Sharma et al, 2020 ; Shi and Brasseur, 2020 ; Wang et al, 2020 ; Isphording and Pestel, 2021 ), regions ( Li et al, 2020 ; Jiang et al, 2021 ; Ma et al, 2021 ; Sulaymon et al, 2021 ; Xian et al, 2021 ), urban ( Adams, 2020 ; Cameletti, 2020 ; Kanniah et al, 2020 ; Kerimray et al, 2020 ; Kumar, 2020 ; Otmani et al, 2020 ; Zangari et al, 2020 ; Zheng et al, 2020 ; Hong et al, 2021 ; Zhao et al, 2021 ), suburban ( Cui et al, 2020 ; Menut et al, 2020 ; Wang et al, 2020 ; Du et al, 2021 ; Hayakawa and Keola, 2021 ; Páez-Osuna et al, 2021 ), and remote areas ( Mandal and Pal, 2020 ). In the transportation sector, many studies concentrated on road traffic ( Ding et al, 2020 ; Dutheil et al, 2020 ; Li et al, 2020 ; Mahato et al, 2020 ; Shehzad et al, 2020 ; Tobías et al, 2020 ; Wang and Su, 2020 ; Xu et al, 2020 ; Chen et al, 2021 ; Hu et al, 2021 ; Rudke et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, most of the existing literatures related to the environmental impact of COVID-19 focused on quantifying the concentration change of atmospheric pollutants in the global context ( Bai et al, 2020 ; Deb et al, 2020 ; Le et al, 2020 ; Dang and Trinh, 2021 ; Keola and Hayakawa, 2021 ; Liu et al, 2021c ; Nguyen et al, 2021 ; Smith et al, 2021 ; Venter et al, 2020 ), countries ( Bao and Zhang, 2020 ; Berman and Ebisu, 2020 ; He et al, 2020 ; Petetin et al, 2020 ; Sharma et al, 2020 ; Shi and Brasseur, 2020 ; Wang et al, 2020 ; Isphording and Pestel, 2021 ), regions ( Li et al, 2020 ; Jiang et al, 2021 ; Ma et al, 2021 ; Sulaymon et al, 2021 ; Xian et al, 2021 ), urban ( Adams, 2020 ; Cameletti, 2020 ; Kanniah et al, 2020 ; Kerimray et al, 2020 ; Kumar, 2020 ; Otmani et al, 2020 ; Zangari et al, 2020 ; Zheng et al, 2020 ; Hong et al, 2021 ; Zhao et al, 2021 ), suburban ( Cui et al, 2020 ; Menut et al, 2020 ; Wang et al, 2020 ; Du et al, 2021 ; Hayakawa and Keola, 2021 ; Páez-Osuna et al, 2021 ), and remote areas ( Mandal and Pal, 2020 ). In the transportation sector, many studies concentrated on road traffic ( Ding et al, 2020 ; Dutheil et al, 2020 ; Li et al, 2020 ; Mahato et al, 2020 ; Shehzad et al, 2020 ; Tobías et al, 2020 ; Wang and Su, 2020 ; Xu et al, 2020 ; Chen et al, 2021 ; Hu et al, 2021 ; Rudke et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many studies have also examined the effect of lockdown orders on air pollution. Although most of these studies investigated the effect for a specific country or region, 1 some studies have examined the effect of lockdowns on the quantity of air pollutants emitted for a global sample (e.g., Dang & Trinh, 2020 ; Deb, Furceri, Ostry, & Tawk, 2020 ; Keola & Hayakawa, 2021 ). These studies have consistently found that lockdown orders decreased the amount of air pollutants emitted.…”
Section: Introductionmentioning
confidence: 99%